Reliability and validity of the Finnish version of the Lower Extremity Functional Scale (LEFS). Issue 12 (5th June 2017) - Repo, Jussi P.; Tukiainen, Erkki J.; Roine, Risto P.; Ilves, Outi; Järvenpää, Salme; Häkkinen, Arja
Abstract: Purpose: The present study aimed to assess the psychometric properties of the Finnish version of the Lower Extremity Functional Scale (LEFS) among foot and ankle patients. Methods: The LEFS was translated and cross-culturally adapted to Finnish. We assessed the test–retest reliability, internal consistency, floor-ceiling effect, construct validity and criterion validity in patients who underwent surgery due to musculoskeletal pathology of the foot and ankle ( N  = 166). Results: The test–retest reliability was high (ICC = 0.93, 95% CI: 0.91–0.95). The standard error of measurement was 4.1 points. The Finnish LEFS showed high internal consistency (Cronbach's α  = 0.96). A slight ceiling effect occurred as 17% achieved the maximum score. The LEFS correlation was strong with the 15D Mobility dimension ( r  = 0.74) and overall HRQoL ( r  = 0.66), pain during foot and ankle activity ( r = −0.69) and stiffness ( r = −0.62). LEFS correlated moderately with foot and ankle pain at rest ( r = −0.50) and with physical activity ( r  = 0.46). Conclusions: The Finnish version of the LEFS showed reliability and validity comparable to those of the original version. This study indicates that the Finnish version of the LEFS serves both clinical and scientific purposes in assessing lower-limb function. Implications for Rehabilitation: The Finnish version of the Lower Extremity Functional Scale (LEFS) is a reliable and valid tool for assessing lower-extremity musculoskeletal disability in Finnish-speaking population. Investigation of the psychometric properties of the Finnish version of the LEFS showed validity and reliability comparable to those of the original English version. The Finnish LEFS is easy to complete and suitable for clinical, rehabilitation and research purposes.